THE EMPLOYMENT RIGHTS AND LEGAL PROTECTION FOR PROFESSIONAL FOOTBALLERS IN MALAYSIAN LABOUR MARKET - Hassim, Jady Zaidi; Zahid, Anowar (International Journal of Business and Society, 2017)
This paper discusses the employment rights of professional footballers in general. The issue to be addressed is whether the rights established in the unilateral and standard blueprint of player agreements can be considered fair for both sides. Indent analysis on this jurisdictional issue significantly concerns the standard terms of an employment contract that influence a professional footballer’s value in the labour market and player transfer policy. This paper adopts a dual methodology of research, namely quantitative and qualitative research. The quantitative data reflect a considerably high level of understanding of the players of the explicitly stated as well as the merely implied contractual terms. However, the majority of footballers are neither individually nor collectively represented in the bargain deal with the employers, which reveals the need of a proper players’ union to transform sports into a labour market which is able to guarantee a stable economic activity. The empowerment of professional sports could generate more marketing revenues and thus enhance human development in professional sports. Keywords: Professional Footballers; Employment Rights; Labour Market; Economic Activity.